Aggregate and sector import price elasticities for a sample of African countries - Chris Jones (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2008)
This paper applies panel data methods to a simple imperfect substitutes model to estimate import demand elasticities for ten African countries. The elasticities are estimated at three levels of aggregation. Firstly, we generate aggregate elasticities for each country. Secondly, we use interactive dummy variables to create estimates for 16 sectors defined by the World Customs Organisation (WCO). Finally, we estimate elasticities for each of the 94 2-digit product lines defined by the Harmonised System (HS). In total there are 10 aggregate estimates, 158 estimates for the 16 WCO sectors; and 911 estimates at the 2-digit level. Using Fixed-Effects, the aggregate estimates do not differ significantly from unity. However, as we move to different levels of aggregation the estimates have much more variability. In general, import demand appears more elastic in sectors that have relatively high levels of domestic production or where there are exports.
Keywords: F14; O55; 330; Imports; Import Demand Elasticities; Africa; Importnachfrage; Außenhandelselastizität; Branche; Methode der kleinsten Quadrate; Afrika